Hepatoprotective And Anti-Oxidant Effect Of Root And Root Callus Extract Of Premna Serratifolia L. In Paracetamol Induced Liver Damage In Male Albino Rats. - C.RAVINDER SINGH; R. NELSON; P.MUTHU KRISHNAN; K.MAHESH (International Journal of Pharma and Bio Sciences, 2011)
Ethanolic extract of root and root derived callus extracts of Premna serratifolia L were investigated against paracetamol induced oxidative stress and hepatotoxicity in blood and liver of male albino rats. The root explants were cultured on MS medium supplemented with various combination and concentration of plant growth regulators. The best callus biomass was observed from the MS medium supplemented with 5.0mg/l of IAA. In the present study, hepatotoxicity induced by paracetamol (800mg/kg) administration was studied by assessing biochemical parameters such as serum glutamate phosphatase (SGOT), serum glutamate pyruvate transanaminase (SGPT), Lactate dehydrogenase (LDH), Lipid peroxidase (LPO), reduced glutathione (GSH), super oxide desmutase (SOD), catalase (CAT), Glutamyl transpeptidase (GT) ascorbic acid (vitamin-C) and α-Tocopherol (Vitamin E). The significant hepatic damage elicited by the levels of hepato specific enzymes such as SGOT, SGPT, LDH and CAT were observed in group one treated with root callus extracts (250 and 500mg) compared with other groups were treated with field grown root extracts (250 and 500mg/ kg). The effects of root callus extracts were comparable to that of standard drug, silymarine. Histopathological findings also suggest that the root callus extracts of Premna serratifolia L, prevents the development of chronic damage. From this present investigation, it can be concluded that the ethanolic extract of root callus is not only an effective hepatoprotective agent but also possess significant antioxidant activity can be attributed to the flavanoid Luteolin and other alkaloids like Premnin, ganikarin and kaniarin which helps to overcome the paracetamol – induced toxicity.